INOVASI BUDIDAYA SAYUR BAYAM SEBAGAI WUJUD MANDIRI PANGAN GUNA MENURUNKAN ANGKA STUNTING DI DESA SUKOSARI - Diki Ardiansyah; Muhammad Rifqi Arya; Poetri Audry Adinda; Achmad Rifa’i; Gendisku Aisyah Prasetyo (CV. ALIM'SPUBLISHING, 2025)
The high rate of stunting is a problem that the government in Indonesia must face. This is due to a spike in stunting cases, the stunting rate in Jember Regency has increased drastically. In Sukosari village itself, the stunting rate according to Ponkesdes data is 29 children. One way to prevent stunting is by using local food, for example spinach which is rich in vitamin A, vitamin C, iron and fiber. The food used is spinach. The implementation phase of this program is in the form of socialization regarding food independence and spinach cultivation with additional cooking demonstrations of innovative spinach nugget products and spinach rolled omelette.